Personalised Hip Therapy: development of a non-operative protocol to treat femoroacetabular impingement syndrome in the FASHIoN randomised controlled trial. Issue 19 (14th September 2016) - Wall, Peter DH; Dickenson, Edward J; Robinson, David; Hughes, Ivor; Realpe, Alba; Hobson, Rachel; Griffin, Damian R; Foster, Nadine E
Abstract : Introduction: Femoroacetabular impingement (FAI) syndrome is increasingly recognised as a cause of hip pain. As part of the design of a randomised controlled trial (RCT) of arthroscopic surgery for FAI syndrome, we developed a protocol for non-operative care and evaluated its feasibility. Methods: In phase one, we developed a protocol for non-operative care for FAI in the UK National Health Service (NHS), through a process of systematic review and consensus gathering. In phase two, the protocol was tested in an internal pilot RCT for protocol adherence and adverse events. Results: The final protocol, called Personalised Hip Therapy (PHT), consists of four core components led by physiotherapists: detailed patient assessment, education and advice, help with pain relief and an exercise-based programme that is individualised, supervised and progressed over time. PHT is delivered over 12–26 weeks in 6–10 physiotherapist-patient contacts, supplemented by a home exercise programme. In the pilot RCT, 42 patients were recruited and 21 randomised to PHT. Review of treatment case report forms, completed by physiotherapists, showed that 13 patients (62%) received treatment that had closely followed the PHT protocol. 13 patients reported some muscle soreness at 6 weeks, but there were no serious adverse events. Conclusion: PHT provides a structure for the non-operative care of FAI and offers guidance to clinicians and researchers in an evolving area with limited evidence. PHT was deliverable within the National Health Service, is safe, and now forms the comparator to arthroscopic surgery in the UK FASHIoN trial (ISRCTN64081839 ). Trial registration number: ISRCTN 09754699.